The persistent gender earnings gap in Colombia, 1994-2006 - Alejandro Hoyos; Hugo \~Nopo; Ximena Pe\~na (Institute for the Study of Labor (IZA), 2010)
This paper surveys gender earnings gaps in Colombia from 1994 to 2006, using matching comparisons to examine the extent to which individuals with similar human capital characteristics earn different wages. Three sub-periods are considered: 1994-1998; 2000-2001; and 2002- 2006, corresponding to the economic cycle of the Colombian economy. The gaps dropped from the first to the second period but remained almost unchanged between the second and the third. The gender earnings gap remains largely unexplained after controlling for different combinations of socio-demographics and job-related characteristics, reaching between 13 and 23 percent of average female earnings. That gap is lower at the middle of the wage distributions than the extremes, possibly due to a gender-equalizing effect of the minimum wage. Moreover, the gap is more pronounced for low-productivity workers and those who need flexibility to participate in labor markets. This suggests that policy interventions in the form of labor market regulations may have little impact on reducing gender earnings gaps.
Keywords: C14; D31; J16; O54; 330; gender; ethnicity; wage gaps; Latin America; Colombia; matching; Lohndifferenzierung; Frauenarbeitslohn; Ethnische Gruppe; Arbeitsproduktivität; Konjunktur; Schätzung; Kolumbien